A multidisciplinary approach to managing unusual complications following corrosive ingestion in a young adult: A case report - Anny Ashiq Ali; Khan, Kashif; Rattani, Salma; Fatima, Dr Samar (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
This case report presents the clinical management of a 24-year-old female patient who was presented to the emergency room with a history of corrosive ingestion. The patient experienced a complex clinical course involving cardiogenic shock, myocarditis, high anion -gap metabolic acidosis, esophagitis, and pulmonary complications. The issue at hand could not have been caused by only corrosive ingestion; it looked like a distinct matter involved. This case highlights the challenges in diagnosing and managing such cases and the importance of a multidisciplinary approach to optimize patient outcomes.